Properties of logarithms, Algebra

Properties of Logarithms

1. logb1 = 0 .  It follows from the fact that bo  = 1.

2. logb b = 1.  It follows from the fact that b 1= b .

3. logb bx  = x .  it can be generalized out to blog b f ( x )  = f ( x ).

4. b logb x  = x .  It can be generalized out to b logb  f ( x )  = f ( x ) .

Properties 3 and 4 lead to a pleasant relationship among the logarithm & exponential function.

Let's first calculate the following function compositions for f ( x )= b x and g ( x ) = logb x .

 ( f o g )( x ) = f [g ( x )] =  f (logb x ) = b logb x  = x

 ( g o f ) ( x ) = g [f ( x )]= g [b x ] = log b bx  = x

Remember again from the section on inverse functions which this means that the exponential & logarithm functions are inverses of each other. It is a nice fact to remember on occasion.

We have to also give the generalized version of Properties 3 & 4 in terms of both the natural and common logarithm

ln e f ( x )  = f ( x)                               log10 f ( x )  = f ( x)

eln f ( x )  = f ( x )                                    10log f ( x )  = f ( x )

Posted Date: 4/8/2013 3:20:54 AM | Location : United States







Related Discussions:- Properties of logarithms, Assignment Help, Ask Question on Properties of logarithms, Get Answer, Expert's Help, Properties of logarithms Discussions

Write discussion on Properties of logarithms
Your posts are moderated
Related Questions
what is the missing angle of 37 degree and 92 drgees

determine slope of 2y = -x + 10

if a-2b=5 then a3-8b3-30ab



mary and susan had a total of 310 stamps. after mary bought another 56 stamps and susan gave away half of her stamps, they both had the same number of stamps. How many stamps did m

hello! at my school we are learning how to solve two-step equations but i am having a little trouble. can you please help me?

To this instance in this chapter we've concentrated on solving out equations.  Now it is time to switch gears a little & begin thinking regarding solving inequalities.  Before we g

Example : Sketch the graph of hyperbolas.                                  ( x - 3) 2 /25 - ( y + 1) 2 /49 =1 Solution Now, notice that the y term contain the minus sig